(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study of a three- and five-level flying capacitor multilevel inverter for a PV system uses phase disposition PWM and phase opposition phase disposition modulation approaches. The control approach of three and five level flying capacitor multilevel inverters uses the multicarrier PWM (MCPWM) techniques phase opposition disposition method. The three and five flying capacitor multilevel inverter is controlled in this study using the in phase disposition PWM controlling approach. MATLAB (2017) was used for the simulation, and the output voltage waveforms are recorded. Comparing the multilayer inverter to the cascaded H-bridge multilevel inverter, it is discovered that the multilevel inverter has less Total Harmonic Distortion (THD).